2020
DOI: 10.3390/w12051361
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Water Supply Management, Household Adaptation, and Drinking Water Quality: A Comparative Study in Two Chinese Provinces

Abstract: Intermittent water supply (IWS) is a relatively common phenomenon across the world as well as in rural and peri-urban areas across China, though there has been little IWS-focused research from China published to date. IWS consumers typically adopt a range of strategies to cope with insufficient water supply, poor drinking water quality, and associated inconveniences. In this study, we collected a range of data from small-scale utilities and households in two IWS systems and two continuous water supply (CWS) sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Of course, there are settings in China and in other LMICs in which centralized drinking water treatment and piped distribution are not feasible. In many such settings in China, government-run mini-utilities provide filling stations where people pay for and collect treated drinking water in large 19 l reusable bottles at costs much closer to those of piped drinking water than retail bottled water [244]. This type of kiosk-model for decentralized drinking water provision offers a relatively affordable and sustainable means of providing access to safe drinking water in regions with low population densities or challenging topography or hydrogeology.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, there are settings in China and in other LMICs in which centralized drinking water treatment and piped distribution are not feasible. In many such settings in China, government-run mini-utilities provide filling stations where people pay for and collect treated drinking water in large 19 l reusable bottles at costs much closer to those of piped drinking water than retail bottled water [244]. This type of kiosk-model for decentralized drinking water provision offers a relatively affordable and sustainable means of providing access to safe drinking water in regions with low population densities or challenging topography or hydrogeology.…”
Section: Discussionmentioning
confidence: 99%
“…Many residents in China's rural areas have the habit of water storage. However, this behavior has certain health risks, and it is easy to cause secondary pollution ( 44 ). Among all the residents who can store water, 51.49% use plastic buckets with no covers to store water, while the rest use self-built water cellars and tanks, where the safety of water is not guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…As such, vulnerable communities' health, livelihoods and well-being are often negatively affected. Li et al (2020), for instance, observed that rural areas experiencing intermittent access to water had lower water usage. They (Li et al 2020) observed behavioural changes such as decreased frequency of washing, hygiene and bathing, as well as inhabitants spending more time and money on water and water storage activities.…”
Section: Consistency In Water Service Provision (Quality Equity)mentioning
confidence: 99%